Simbolizem krvi, spremenjena stanja in plodnost - Terčelj, Marija Mojca (Etnolog. Nova vrsta (Ljubljana), 2000)
The article searches for a more complex explanation of the agricultural symbolism of the Zoque Indians, based on a comparative analysis of the concept of human body, especially of its blood and its magical therapeutic function, the fertility ritual of the "Three Virgins of Copoya" and the myth about the "Volcano" woman. The article is based on two separate researches among the Zoques of Chiapas, which the author carried out in the villages of Pantepec and Copoya, and in the town of Tuxtla Gutiérrez between 1990 and 1997.
Keywords: ethnology; etnologija; anthropology; antropologija; medicina; medicine; Mehika; Mexico; Indijanci; Sokeji; telo; kri; plodnost; magija